2009
DOI: 10.1089/mdr.2009.0915
|View full text |Cite
|
Sign up to set email alerts
|

Two Closely Related Fluconazole-Resistant Candida tropicalis Clones Circulating in Taiwan from 1999 to 2006

Abstract: Recently, we reported that diploid sequence type (DST) 140 was a predominant type of Candida tropicalis among isolates with fluconazole minimum inhibitory concentrations (MICs) >or=64 microg/ml collected in the Taiwan Surveillance of Antimicrobial Resistance of Yeasts (TSARY) in 1999. To determine if DST140 persists in Taiwan, we have used multilocus sequence typing to characterize the genetic profiles of 31 resistant isolates (MICs >or=64 microg/ml), together with 19 susceptible isolates (MICs Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The four clusters comprised 48.7% of the fluconazole non-susceptible isolates overall. Previous studies in Taiwan also observed regional dissemination of genetically close-related fluconazole-resistant C. tropicalis isolates (Chou et al, 2007; Li et al, 2009). Therefore, continuous monitoring of the fluconazole non-susceptible C. tropicalis isolates assisted by molecular typing assays is warranted.…”
Section: Discussionmentioning
confidence: 71%
“…The four clusters comprised 48.7% of the fluconazole non-susceptible isolates overall. Previous studies in Taiwan also observed regional dissemination of genetically close-related fluconazole-resistant C. tropicalis isolates (Chou et al, 2007; Li et al, 2009). Therefore, continuous monitoring of the fluconazole non-susceptible C. tropicalis isolates assisted by molecular typing assays is warranted.…”
Section: Discussionmentioning
confidence: 71%
“…On the other hand, we did not find the Y132F and S145F substitutions in our isolates. Because increased resistance of C. tropicalis to fluconazole and outbreaks of infection caused by fluconazole-resistant C. tropicalis have been recognized in some hospitals (5,25,26), C. tropicalis isolates with the ERG11 mutation should be genotyped to investigate the transmission of particular clones. Although overexpression of ERG11 associated with missense mutations has been described as the mechanism of azole resistance in clinical isolates of C. tropicalis (7,8), in the present study, only two FNS isolates harbored ERG11 mutations, suggesting that gene overexpression, rather than ERG11 mutation, is the main mechanism of azole resistance in C. tropicalis isolates from Korean hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Chou et al (27) also reported an association between the DSTs and the C. tropicalis trailing phenomenon. Additionally, Li et al (36) described several alleles associated with low MICs of fluconazole (alleles 3 of ICL1, 9 of MDR1, 1 of SAPT2, 3, 6, and 10 of SAPT4, 48 of XYR1, and 7 of ZWF1a). In our study, we found no isolate with DST 140, and there was an association of allele 48 (XYR1) and allele 6 (SAPT4) with fluconazole-susceptible and fluconazole-resistant isolates, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…MLST has been used to establish the relationship between the DSTs with susceptibility profile to fluconazole and the trailing phenomenon (27,32,36). In Brazil, fluconazole is an effective systemic antifungal drug against most isolates of C. tropicalis (24).…”
mentioning
confidence: 99%